Kendala-Kendala Belajar Siswa Tingkat Dasar Selama Pembelajaran Terbatas - Asni, Asni; Sari, Rita; Rahayu, Nina (Diksi: Jurnal Pendidikan dan Literasi, 2023)
The purpose of the study was to determine the learning difficulties of primary-level students in online learning in Birem Rayeuk Village. The type used in the research is a descriptive survey. The research findings show that some of the obstacles during limited learning are problems (1) the internet network is unstable; (2) the internet quota is very inadequate; (3) too many homework assignments given by the teacher every day; (4) students find it difficult to focus when learning the subject matter; (5) the applications used are difficult for students to understand. The second finding is that teachers' efforts to optimize limited learning include (1) forming study groups; (2) conducting home visits; (3) making learning videos according to the theme; and (4) cooperating with student guardians in accompanying children to study at home.